THE INFLUENCE OF CHARACTERISTICS AND SOURCES OF INFORMATION ON PREMARITAL SEXUAL BEHAVIOR IN STUDENTS IN THE NURSING ACADEMY FROM MEDAN IN 2019 - RENY JULIANA SIHOMBING; ELISABETH DAME MANALU; FRISKA ERNITA SITORUS (LP2MTBM MAKARIOZ, 2020)
Charateristic is personality influenced by motivation that support person to act. So, someone’s personality shows an actiondue to afirm and strong willingness and it scharateristik or vice versa. This time, the most problem of adolescents inIndonesia that consists of 60% adolescents admitted to practive sex and the other that consists of 50% of people living withHIV werethe group isadolescents. The negative consequences of sex behavior which causes an Indonesian teenagerdisrupted opportunities continue study at school, enter the work force, starting become a family and become a member ofsociety as well. The increasing premarital sexual behavior impact on prenancy outsidemarriage.The objective of study was toanalyze of student charateristic on gender,resisdence, relationship and sources of information (parent’s role, friends, andmedia) towards having sexual relations. The study was anlytical with a cross sectional design. The population in this studywere 55 studens of (Darmo Nursing Academy/studend) Medan who are in level 1, level 2 and level 3.Based on the results ofthe study, it was found that the variables significanty the tendence of having sexual intercource were sex (p = 000),residence (p = 000) relatinship (p = 0, 000) and souerce of information (p = 0,000). The most dominant variables ofinfluencing premarital sex are gender, relationship, and sources of information. It is recomended for education authorites toimprove religius curriculum in university so that students are afraid of sin to have premarital sex.